2006
DOI: 10.1175/bams-87-5-585
|View full text |Cite
|
Sign up to set email alerts
|

What Do Networks Have to Do with Climate?

Abstract: Advances in understanding coupling in complex networks offer new ways of studying the collective behavior of interactive systems and already have yielded new insights in many areas of science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
317
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(324 citation statements)
references
References 47 publications
7
317
0
Order By: Relevance
“…Instead of considering the time dependence of climate records at single grid points i, we study the time evolution of the interactions (teleconnections) between pairs of grid points i and j, which are represented by the strengths of the cross-correlations between the climate records at these sites. The interactions can be considered as links in a climate network where the nodes are the grid points (31)(32)(33)(34). Recent empirical studies have shown that in the large-scale climate network the links tend to weaken significantly during El Niño episodes, and this phenomenon is most pronounced for those links that connect the "El Niño basin" (solid circles in Fig.…”
mentioning
confidence: 99%
“…Instead of considering the time dependence of climate records at single grid points i, we study the time evolution of the interactions (teleconnections) between pairs of grid points i and j, which are represented by the strengths of the cross-correlations between the climate records at these sites. The interactions can be considered as links in a climate network where the nodes are the grid points (31)(32)(33)(34). Recent empirical studies have shown that in the large-scale climate network the links tend to weaken significantly during El Niño episodes, and this phenomenon is most pronounced for those links that connect the "El Niño basin" (solid circles in Fig.…”
mentioning
confidence: 99%
“…To resolve this problem, we recently introduced an alternative forecasting approach (31) based on complex networks analysis (32)(33)(34)(35) that can considerably shift the probabilistic prediction horizon. The approach exploits the remarkable observation that a large-scale cooperative mode linking the "El Niño basin" (i.e., the equatorial Pacific corridor) and the rest of the Pacific ocean ( Fig.…”
mentioning
confidence: 99%
“…It was recently suggested that climate fields such as temperature and geopotential height at a certain pressure level can be represented as a climate network [1]. In this network, different regions of the world are represented as nodes which communicate by exchanging heat, material, and by direct forces.…”
mentioning
confidence: 99%